Synthesis of 6, 13-dihydro-6, 13-ethanopentacene-15, 16-diimine palladium(II) complex and steric effect of the backbone polycyclic aromatic system on palladium-catalyzed olefin polymerization. Issue 11 (November 2019) - Huo, Ping; Yuan, Lin; Liu, Wanyun; Liu, Lin; Mei, Guangquan
The synthesis and characterization of a novel 6, 13-dihydro-6, 13-ethanopentacene-15, 16-diimine palladium(II) complex are described. The effect of the backbone framework of the α-diimine metal catalyst on the polymerization reaction of norbornene and 1-octene is investigated. Compared to the 9, 10-dihydro-9, 10-ethanoanthracene-11, 12-diimine palladium(II) complex (C1 ), the 6, 13-dihydro-6, 13-ethanopentacene-15, 16-diimine palladium(II) complex (C2 ) with a polycyclic aromatic system on the backbone exhibits relatively high activities and leads to high molecular weights as well as narrow molecular weight distributions depending on the variation in feed ratios for copolymerization of norbornene and 1-octene. Moreover, the copolymers obtained using the 6, 13-dihydro-6, 13-ethanopentacene-15, 16-diimine palladium(II) complex (C2 ) with large steric hindrance show high thermal stability and high glass transition temperatures.